The Effect Of Educational Videos On The Level Pregnant Women's Knowledge About Delivery By A Paragon In Kebadu Village - -, Indrawasih; Fadhilah, Siti; Ismawati, Riska (Jurnal Maternitas Kebidanan, 2025)
Complications from pregnancy or childbirth cause 287,000 women to die each year, mostly in low-income countries, where many deaths could be prevented by qualified health workers. Video is an educational tool that engages multiple senses and can lead to better outcomes.To assess how educational videos impact the knowledge of expectant mothers regarding childbirth by paraji in Kebadu Village, Balai District, Sanggau Regency. The study employs a pre-experimental design featuring a single-group pretest-posttest setup. The participants in this research were all expectant mothers in trimester 1 to trimester 3 from February - May 2024, namely 37 pregnant women. The sample in this study was 37 pregnant women in trimester 1 to trimester 3. The level of knowledge of expectant mothers prior to receiving education showed a good understanding with 20 individuals (54.1%). The understanding of expectant mothers after receiving education was good knowledge with 34 individuals (91.1%). There is a difference in the level of knowledge of pregnant women before and after being given education about childbirth by Paraji in Kebadu Village (0.000 <α 0.05).